PERAN MEDIASI JOB SATISFACTION DALAM PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN SELF-MANAGEMENT TERHADAP PERFORMANCE (Polisi Sabhara pada Masa Pandemi COVID-19 di Karawang, Jawa Barat) - Sinta Gisthi Ardhiani, - (2022)
Organizational citizenship behavior and self-management make humans more meaningful, especially in building the performance of an organization. Performance accompanied by a sense of sincerity and optimism in themselves and mentally healthy members make the organization rich in human resources. The viral hashtag #percumalaporpolisi raises a bad stigma in society against the performance of the police of the republic of Indonesia. As humans who work in government organizations with community social problems and various pressures in the community both offline and online, especially during the covid19 pandemic, Polri's self-management, mental health of the police who are at the forefront need to be in the spotlight of various parties. This study aims to obtain an overview of organizational citizenship behavior, self-management, job satisfaction, and performance as well as the magnitude of the relationship between these four variables in members of the sabhara police force of Karawang Police, totaling 102 police officers as respondents. The type of research used is descriptive and verification. The data analysis technique used is bust linear regression with SPSS calculator and manual calculations. The findings of this study indicate that the descriptions of all variables within the police are in the very high category and influence each other directly. except that police OCB and police self-management have no direct effect on performance. However, the existence of job satisfaction as a mediator is able to indirectly mediate the influence of OCB and self-management on performance.